Enhancing Productivity and Family Income Through Development of Coffee Plant Breeding and Postharvest Handling Technology - I Gede Pasek Mangku; Yohanes Parlindungan Situmeang; Ni Luh Putu Indiani; Naori Miyazawa (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
the UUT group's family income. Agrosemesta aims to increase the productivity, capabilities, and skills of farmers' groups in the coffee business. This activity aimed to improve coffee farmers' knowledge, skills, and capabilities in breeding coffee plants, green bean storage, and marketing strategies. The method used consists of surveys, observations, mentoring, knowledge transfer, practice, documentation, and evaluation. The result showed that the UUT group. Agrosemesta has sufficient knowledge and skills to develop coffee breeding programs and has used social media to promote and increase market access. Otherwise, in terms of storage, green beans are not yet stored properly in the warehouse. The group did not use temperature and humidity control during green bean storage due to limited financial and skill resources. However, the group has a strong commitment to improving breeding techniques for coffee plants, green bean storage, and the marketing strategy to grow the coffee business in the future. Contribution to Sustainable Development Goals (SDGs):SDG 2 : Zero HungerSDG 9 : Industry, Innovation, and InfrastructureSDG 12 : Responsible Consumption and Production